2002
DOI: 10.1074/jbc.m110976200
|View full text |Cite
|
Sign up to set email alerts
|

Liprin β1, a Member of the Family of LAR Transmembrane Tyrosine Phosphatase-interacting Proteins, Is a New Target for the Metastasis-associated Protein S100A4 (Mts1)

Abstract: Metastasis-associated protein S100A4 (Mts1) induces invasiveness of primary tumors and promotes metastasis. S100A4 belongs to the family of small calcium-binding S100 proteins that are involved in different cellular processes as transducers of calcium signal. S100A4 modulates properties of tumor cells via interaction with its intracellular targets, heavy chain of non-muscle myosin and p53. Here we report identification of a new molecular target of the S100A4 protein, liprin ␤1. Liprin ␤1 belongs to the family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
98
1
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 124 publications
(104 citation statements)
references
References 43 publications
2
98
1
2
Order By: Relevance
“…Several glycosylation sites are known for Tag7 protein, 16 and Mts1 can be phosphorylated by PKC. 33 In addition, our results demonstrated that Mts1 in a leukocyte conditioned medium can be in 2 alternative forms, monomeric and tetrameric, and these properties of Mts1, possibly, could affect the chemotactic activity of the Tag7-Mts1 complex. It is also worth noting that other proteins could interact with the Tag7-Mts1 complex.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Several glycosylation sites are known for Tag7 protein, 16 and Mts1 can be phosphorylated by PKC. 33 In addition, our results demonstrated that Mts1 in a leukocyte conditioned medium can be in 2 alternative forms, monomeric and tetrameric, and these properties of Mts1, possibly, could affect the chemotactic activity of the Tag7-Mts1 complex. It is also worth noting that other proteins could interact with the Tag7-Mts1 complex.…”
Section: Discussionmentioning
confidence: 89%
“…Proteins were visualized using ECL Plus detection reagents (GE Healthcare) according to the manufacturer's protocol. The contents of Mts1 33 and Tag7 20 in samples were measured by a ELISA.…”
Section: Methodsmentioning
confidence: 99%
“…[13][14][15] S100A4 also induces a migratory phenotype by affecting cell adhesion via binding to liprin ␤1. 16 Moreover, S100A4 binds to the tumor suppressor p53 and modulates its transcriptional activity. 17 Extracellular S100A4 activates expression of several matrix metalloproteinases, thereby enabling cell invasion into adjacent tissues and facilitating angiogenesis.…”
mentioning
confidence: 99%
“…The poor outlook for cancer patients with elevated expression of S100A4 is likely to be due to the ability of S100A4 to induce a metastatic phenotype; however, the mechanism of the strong metastasisinducing properties of S100A4 is not known. S100A4 has been reported to interact with a number of protein targets, at least in vitro, namely nonmuscle tropomyosin (Takenaga et al, 1994), nonmuscle myosin A heavy chain (Kriajevska et al, 1994;Ford and Zain, 1995), p53 (Grigorian et al, 2001), liprin b1 (Kriajevska et al, 2002) and methionine aminopeptidase 2 (Endo et al, 2002). S100A4 also self-associates to form a homodimer as shown by its NMR structure (Vallely et al, 2002).…”
Section: Introductionmentioning
confidence: 99%